2012
DOI: 10.1038/ja.2012.83
|View full text |Cite
|
Sign up to set email alerts
|

Spirohexalines, new inhibitors of bacterial undecaprenyl pyrophosphate synthase, produced by Penicillium brasilianum FKI-3368

Abstract: An enzyme assay for bacterial undecaprenyl pyrophosphate (UPP) synthase was performed to screen microbial culture broths for inhibitors of UPP synthase. During the course of this screening program, an EtOH extract of a rice culture of Penicillium brasilianum FKI-3368 was found to inhibit UPP synthase activity. From activity-guided purification, a new compound-designated spirohexaline was isolated together with the structurally related and known viridicatumtoxin by ethyl acetate extraction silica gel and octade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 19 publications
2
61
0
3
Order By: Relevance
“…The other known compounds isolated from P. kongii including pebrolide (Mccorkindale et al 1981) ( 2 ), 1-deoxypebrolide (Mccorkindale et al 1981) ( 3 ), asperphenamate (McCorkindale et al 1978) ( 4 ), N-benzoyl-phenylalaninol (McCorkindale et al 1978) ( 8 ), orsellinic acid (Fang et al 2012) ( 9 ), mycophenolic acid (Makara et al 1996) ( 10 ), and 5, 7-dihydroxy-4-methylphthalide (Fujimoto et al 1999) ( 11 ), and the other known compounds isolated from P. brasilianum including 12, 13-dihydroxyfumitremorgin C (Inokoshi et al 2013) ( 12 ), verruculogen (Afiyatullov et al 2004) ( 13 ), viridicatumtoxin (Inokoshi et al 2013) ( 14 ), dehydroaustin (Hayashi et al 1994) ( 15 ), austinolide (Lo et al 2012) ( 16 ), neoaustin (Hayashi et al 1994) ( 17 ), brasiliamide A (Fujita et al 2002) ( 18 ), brasiliamide C (Fujita & Hayashi 2004) ( 19 ), and aspterric acid (Shimada et al 2002) ( 20 ), were determined by comparison of those reported spectroscopic data. Among these, aspterric acid is reported from P. brasilianum for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The other known compounds isolated from P. kongii including pebrolide (Mccorkindale et al 1981) ( 2 ), 1-deoxypebrolide (Mccorkindale et al 1981) ( 3 ), asperphenamate (McCorkindale et al 1978) ( 4 ), N-benzoyl-phenylalaninol (McCorkindale et al 1978) ( 8 ), orsellinic acid (Fang et al 2012) ( 9 ), mycophenolic acid (Makara et al 1996) ( 10 ), and 5, 7-dihydroxy-4-methylphthalide (Fujimoto et al 1999) ( 11 ), and the other known compounds isolated from P. brasilianum including 12, 13-dihydroxyfumitremorgin C (Inokoshi et al 2013) ( 12 ), verruculogen (Afiyatullov et al 2004) ( 13 ), viridicatumtoxin (Inokoshi et al 2013) ( 14 ), dehydroaustin (Hayashi et al 1994) ( 15 ), austinolide (Lo et al 2012) ( 16 ), neoaustin (Hayashi et al 1994) ( 17 ), brasiliamide A (Fujita et al 2002) ( 18 ), brasiliamide C (Fujita & Hayashi 2004) ( 19 ), and aspterric acid (Shimada et al 2002) ( 20 ), were determined by comparison of those reported spectroscopic data. Among these, aspterric acid is reported from P. brasilianum for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…C 55 -P also serves as a carrier in the synthesis of peptidoglycan as well as various other cell wall components such as wall teichoic acids, lipopolysaccharide, and O-antigens (5-7). Considerable effort has been devoted to the identification of selective UppS inhibitors as lead compounds for antibiotic development (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Spirohexaline and structurally related viridicatumtoxin were isolated from a fungal culture of Penicillium brasilianum FKI-3368. 22) These compounds inhibited UPP synthase activity with IC 50 values of 9.0 and 4.0 µM, and exhibited anti-MRSA activity with MICs of 1.56 and 6.25 µg/mL, respectively. From further selectivity studies, these were found to more selectively inhibit UPP synthase than the functionally related enzymes, octaprenyl pyrophosphate synthase from Escherichia (E.) coli and mammalian dehydrodolichyl pyrophosphate synthase.…”
Section: Screening For Inhibitors Of Mrsa Undecaprenyl Pyrophosphate mentioning
confidence: 93%
“…The amount of pyrophosphate produced by the enzyme was determined according to the established method. 21) IPP-derived pyrophosphate was hydrolyzed by inorganic pyrophosphatase 22) to determine the amount of phosphate. As a practical screening strategy, a total of 12118 cultures (5941 actinomycetes and 6177 fungi) were first screened for antimicrobial activity against S. aureus and Bacillus subtilis.…”
Section: Screening For Inhibitors Of Mrsa Undecaprenyl Pyrophosphate mentioning
confidence: 99%